Deep soft-tissue leiomyoma of the forearm mimicking a primary bone tumor of the ulna - Ramachandran, Rajoo (Radiol Case Rep, 2015)
Leiomyomas of the soft tissues are rare in general, and extremely uncommon in the forearm. In general, leiomyomas are benign soft-tissue tumors that occur where smooth muscles are present. We present a case of soft-tissue leiomyoma of the forearm eroding the midshaft of the ulna, with emphasis on radiological diagnosis and histopathological correlation.